The Effect of Sports Massage on Physical Fitness in IPNG Teqball Athletes in 2024/2025 - Herlina, Herlina; Burhan, Zakir; Ashari, Lalu Hasan (Lembaga Penelitian dan Pendidikan Mandala, 2025)
This study aims to determine the effect of providing sport massage on physical fitness in UKM Teqball IPNG athletes in 2024/2025. This study used a quantitative method with a descriptive design with one group pretest-posttest without a control group. The sample in this study were 10 athletes from the IPNG Teqball UKM who were selected based on certain criteria. The instrument used to measure physical fitness was a fitness test conducted before and after treatment. Data were analyzed using normality and homogeneity tests to ensure the feasibility of the parametric test. The results of the homogeneity test showed that the data had the same variance, with a significance value of 0.104 greater than 0.05. Furthermore, a Paired Sample T-Test was used to see the difference in pretest and post-test scores. The results of the analysis showed an average difference of -10.7400, and a significance value (2-tailed) of 0.001. This value is smaller than 0.05, thus indicating a significant effect between the administration of sport massage on the physical fitness of athletes. Based on these results, it can be concluded that sport massage can be used as an effective recovery method to improve the overall physical condition of athletes.